PENGARUH MOTIVASI BELAJAR MATEMATIKA TERHADAP HASIL BELAJAR SISWA KELAS IV SDN 127 INPRES MONCONGLOE KABUPATEN MAROS - Cytra, Yulia; Reskiana; Nur'Abidah, Hafidzah; Salzabila, Mutiara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted based on the problem of low student engagement and suboptimal mathematics learning outcomes among fourth-grade students at SDN 127 Inpres Moncongloe. The research aimed to determine the effect of mathematics learning motivation on students’ learning outcomes. This study used a quantitative approach with an ex-post facto design. The population consisted of 97 students, while the sample was 22 students selected using purposive sampling based on data availability and research needs. Data were collected through a motivation questionnaire and documentation of mathematics test scores. Data analysis included descriptive statistics to describe the condition of each variable, followed by prerequisite tests consisting of normality and linearity tests. Hypothesis testing was conducted using simple linear regression analysis, supported by t-test and coefficient of determination to measure the strength and contribution of the relationship between variables. The results showed that learning motivation has a positive and significant effect on mathematics learning outcomes. This is indicated by a significance value less than 0.05 and a regression coefficient of 1.737, meaning that every increase in motivation score is followed by an increase in learning outcomes. The correlation coefficient of 0.958 indicates a very strong relationship between motivation and learning outcomes. In addition, the coefficient of determination (R²) of 0.918 shows that 91.8% of learning outcomes are influenced by learning motivation. These findings indicate that motivation plays a major role in improving students’ mathematics learning outcomes and supports efforts to enhance student engagement in the learning process.